Implementasi Kurikulum Merdeka Dalam Pembelajaran Bahasa Indonesia Di Sekolah - Dian Sansiska Pratiwi (Prodi PGSD Unsultra, 2023)
The implementation of the Merdeka Curriculum in Indonesian language learning at schools is a crucial effort to enhance the quality of education in Indonesia. The Merdeka Curriculum offers flexibility that allows teachers to adjust learning according to the needs and characteristics of students. This article reviews various studies related to the implementation of the Merdeka Curriculum, with a focus on its application in Indonesian language education at the elementary and secondary school levels. The analysis results indicate that although there are challenges in implementation, the Merdeka Curriculum can improve students' language skills, both oral and written, through a more contextual and experience-based approach. This article also discusses the importance of the teacher's role, the utilization of technology, and the development of teaching materials in supporting the success of this curriculum.